A pilot study of the feasibility of a Swedish multimodal group intervention for severe migraine—The migraine patient school. (17th June 2021) - Helmerson, Birgitta; Sundholm, Anna; Hedborg, Kerstin; Waldenlind, Elisabet; Kierkegaard, Marie; Remahl, A Ingela M Nilsson
Objectives: To evaluate a multidisciplinary group intervention, the migraine patient school (MPS), for patients with severe, mostly chronic migraine. Method: A 13-week group intervention program including seven sessions of patient education, practical body awareness and relaxation exercises, and home assignments was performed in small groups with 5–11 participants. Four groups were consecutively included from spring 2014 to fall 2015. Headache diaries and standardized and study-specific questionnaires were used for evaluation at baseline before MPS (pre-interventional phase), and at follow-up. Results: Twenty-four of 30 included patients completed the study, i.e. attended ≥ four sessions. Most participants found it rewarding to participate in the MPS and easy to take part in, understand and complete home assignments. Validated standardized questionnaires delivered before, and after (follow-up) MPS showed that the impact on life (HIT-6) and avoidance behavior (PIPS-A) were significantly improved whereas quality of life (MSQL), anxiety and depression (HAD) and perceived stress (PSS-14) did not show a statistically significant change. Conclusion: The Migraine patient school with a multimodal educational and behavioral group intervention program was feasible to perform and seem to benefit patients with severe (high-frequency or chronic) migraine.